De Stijl Style Board Design Of Waste Processing Of HDPE and LDPE Plastic Bags - Ningroom - Adiani; Andina Rizky Fitri (Jurnal IPTEK, 2022)
The classification of plastic bag waste made from HDPE and LDPE is based on colour obtained white and black in dominant quantities in addition to red, blue, yellow, and others. Through the experimental method, heating on a gas stove at a temperature of 40-700C can melt the plastic bag waste. Heating is done to meet the trash so that it can be manually moulded into various geometric shapes. Selection of the optimal shape and size of the mould is needed to realize the geometric board shape. De Stijl's style in Piet Mondrian's 2D work is used as the basis for composing the printed composition. The design method is used to realize the arrangement into a geometric board shape with a colour composition in De Stijl's modernism style. The boards will be resin reinforced by the FRP method. The board is used to make stool products, pegboards and corner tables.